A study on the role of influence group in public policy making - Abbas Monavarian; Mojtaba Amiri; Narges Sadat Razavimehr (Management Science Letters)
Nowadays, learning more about influence groups on public policy making is one of most important subjects of management science. Governments are the primary sources for public policy making but influenced groups participate indirectly and while they remain out of power, they put pressure on many decisions. Some of participants in public policy making are not influenced groups but mostly, due to their participation in policy public making matter are called influenced groups. This research, from practical research purpose and method view, is a descriptive research and survey branch. The study investigates the effect of university based Iranian Sociological Association on public policy making. The study designs a questionnaire in Likert scale and distributes it among some experts. The results of our survey indicate that that Iranian Sociological Association could influence on public policy making through elite and prominent leaders, self-knowledge and information, elective campaigns, stimulation and connecting with people and other groups.